2016
DOI: 10.18632/oncotarget.7410
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-sensors, enigmatic-orphan and orphan nuclear receptors as therapeutic targets in breast-cancer

Abstract: Breast-cancer is heterogeneous and consists of various groups with different biological characteristics. Innovative pharmacological approaches accounting for this heterogeneity are needed. The forty eight human Nuclear-Hormone-Receptors are ligand-dependent transcription-factors and are classified into Endocrine-Receptors, Adopted-Orphan-Receptors (Lipid-sensors and Enigmatic-Orphans) and Orphan-receptors. Nuclear-Receptors represent ideal targets for the design/synthesis of pharmacological ligands. We provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 139 publications
6
25
0
Order By: Relevance
“…2b). In TCGA data, we confirmed the previously published findings of Garattini, et al [13] and found that BLBC patients had significantly lower ESRRB expression compared to luminal A patients ( Fig. 2c).…”
Section: Esrrb Mrna Expression Levels Are Significantly Decreased In supporting
confidence: 91%
See 1 more Smart Citation
“…2b). In TCGA data, we confirmed the previously published findings of Garattini, et al [13] and found that BLBC patients had significantly lower ESRRB expression compared to luminal A patients ( Fig. 2c).…”
Section: Esrrb Mrna Expression Levels Are Significantly Decreased In supporting
confidence: 91%
“…Our 2016 publication showed that BLBC patients with high ESRRB mRNA expression have significantly improved distant-metastases free, and recurrence-free survival in comparison to patients with low expression [11]. Previous publications have shown that BLBC patients overall have significantly lower ESRRB mRNA expression in comparison to other breast cancer subtypes [12,13].…”
Section: Introductionmentioning
confidence: 78%
“…No probesets that can detect ERRβsf (alone or in combination with others) are available on this Affymetrix platform. Garattini et al's recent analysis of nuclear receptor superfamily expression in The Cancer Genome Atlas (TCGA) breast cancer RNAseq data shows that total ESRRB expression (referred to in the manuscript as NR3B2) is significantly reduced in breast tumors vs. normal breast tissue, with lowest expression in the Luminal B and Basal-Like molecular subtypes [90]. While preliminary, these data suggest that ERRβ2 may be a good prognostic factor in TNBC, and are consistent with the findings we present here that implicate the activated ERRβ2 splice variant as a potent inhibitor of mitotic progression in breast cancer cells, including triple negative models.…”
Section: Discussionmentioning
confidence: 99%
“…We further revealed that environmentally induced oxidative stress decreased the level and homo-dimerization activity of NR2E3, resulting in a repressive epigenetic status of ESR1 gene promoter by LSD1 recruitment, consequently turning off ESR1 expression, indicating that NR2E3 is an oxidative stress-responsive epigenetic regulator 7 . Furthermore, ligand-activated potential of NR2E3 like other orphan nuclear receptors will provide opportunity to develop therapeutic targets in the future, although no ligand identified yet 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%